Mindfulness and consumer behavior: a bibliometric analysis of themes and trends over 20 years - Maria-Angeles Iniesta-Bonillo; Alinne Pompeu-Queiros; Maria Mercedes Capobianco Uriarte; Helena Alves (Humanities & Social Sciences Communications)
Abstract Mindlessness, or lack of awareness, is deeply rooted in society and reinforced by the constant stimuli from marketing practices, leading to unhealthy and unsustainable consequences for individuals, society, and the environment. In consumer behavior, this manifests as impulsive or excessive purchasing, which undermines well-being and happiness rather than enhancing them. Mindfulness has emerged as a potential solution to mindless consumption that, fostering change from the inside out, not only benefits personal well-being but also contributes to the broader well-being of society. Consumer behavior and mindfulness have been studied independently in fields such as psychology and sociology for several decades. However, the joint study and application of these areas have gained prominence in recent years, driven by the expanding practice and growing academic interest in mindfulness. This paper aims to contribute to this research field by conducting a comprehensive analysis of the key elements that shape and drive research in mindfulness and consumer behavior over the past two decades. Using a bibliometric analysis of 198 articles from the Web of Science and Scopus databases, the study identifies leading authors, institutions, countries, journals, and collaborative research networks, along with core thematic areas within the field. This research can serve as a foundation for future research and guide organizations and institutions in understanding potential shifts in consumer behavior associated with mindfulness practices. By positioning mindfulness as an integral part of the transformation in consumption behaviors, organizations may support and adapt to a more harmonious and sustainable future centered on universal well-being and the prioritization of beneficial consumption practices.